2002
DOI: 10.1091/mbc.e02-05-0272
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Profiling ofCandida albicansCells Undergoing the Yeast-to-Hyphal Transition

Abstract: The ability of the pathogenic fungus Candida albicans to switch from a yeast to a hyphal morphology in response to external signals is implicated in its pathogenicity. We used glass DNA microarrays to investigate the transcription profiles of 6333 predicted ORFs in cells undergoing this transition and their responses to changes in temperature and culture medium. We have identified several genes whose transcriptional profiles are similar to those of known virulence factors that are modulated by the switch to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
380
1
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(416 citation statements)
references
References 66 publications
28
380
1
7
Order By: Relevance
“…These include all known hypha-specific genes on the microarray ( Figure 5A). IHD1, identified in a genome-wide transcriptional profiling of genes induced or repressed during hyphal development by Nantel et al (2002), was also found in this cluster, and further confirmed by Northern analysis ( Figure 5B). The gene was independently found by Murad et al (2001) as one of the genes regulated by the Nrg1 and Tup1 repressors.…”
Section: Flo8 Is Required For Expressing Subsets Of Efg1-regulated Genessupporting
confidence: 64%
“…These include all known hypha-specific genes on the microarray ( Figure 5A). IHD1, identified in a genome-wide transcriptional profiling of genes induced or repressed during hyphal development by Nantel et al (2002), was also found in this cluster, and further confirmed by Northern analysis ( Figure 5B). The gene was independently found by Murad et al (2001) as one of the genes regulated by the Nrg1 and Tup1 repressors.…”
Section: Flo8 Is Required For Expressing Subsets Of Efg1-regulated Genessupporting
confidence: 64%
“…Therefore, the lack of Grx (due to GRX2 disruption) and GSSH accumulation may partially explain the inability to form hyphae in the double mutant, i.e., due to ROS accumulation. SOD5 has been demonstrated to relate to hyphae formation by transcript profiling; i.e., this gene is up-regulated during the process of hyphae formation (Nantel et al 2002) Furthermore, Martchenko et al (2004 demonstrated with Northern analysis that SOD5 expression during hyphae formation is due to the presence of serum. SOD1 is also transcribed in the presence of serum (Lamarre et al 2001), which could explain why a double mutant for two oxidative stress genes (GRX2 and SOD1) is defective in hyphae formation.…”
Section: Discussionmentioning
confidence: 99%
“…SOD5 expression is increased in C. albicans yeast cells exposed to PMNs (Fradin et al 2005) and during morphological change from yeasts to hyphae (Nantel et al 2002). However, while sod1Δ is hypersensitive to killing by a macrophage cell line in vitro (Hwang et al 2002), the same was not observed for sod5Δ (Martchenko et al 2004), indicating that the virulence role of Sod5 may be due to a resistance to different phagocytic cells.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Probes, chip hybridization, and quantification. Most of the transcript profiling in this study used Cy3-and Cy5-labeled cDNA probes that were produced from approximately 3 to 5 g of poly(A)(ϩ) RNA and hybridized, as described previously, to microarrays spotted with amplicons from 6,002 putative open reading frames (39). For each condition, at least three independent experiments with reciprocal labeling were done, for a total of six individual hybridizations, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%